Hidradenitis suppurativa: epidemiological study of cases diagnosed at a dermatological reference center in the city of Bauru, in the Brazilian southeast State of São Paulo, between 2005 and 2015 - Tatiana Cristina Pedro Cordeiro de Andrade; Bruna Cortinóvis Vieira; Agnes Mayumi Nakano Oliveira; Tábata Yamasaki Martins; Tatiane Meira Santiago; Antônio Carlos Ceribelli Martelli (Anais Brasileiros de Dermatologia, 2017)
Abstract: Background: Hidradenitis is a chronic inflammatory disease of the hair follicles. A treatment is necessary due to chronicity and psychological changes that patient present. Objective: To investigate epidemiological aspects and elaborate a risk group profile, promote early diagnosis and contribute to the knowledge about the disease. Methods: This cross-sectional descriptive study with retrospective analysis of medical records of 194 patients diagnosed with hidrosadenitis in a dermatological reference center in the city of Bauru (SP) between 2005 and 2015. Results: Females accounted for 74% of cases. The age at diagnosis ranged from 10 to 67 years and the majority was within the 3rd and 4th decade of life. It occurred Association with diabetes mellitus in 33%, obesity in 55% and smoking in 61% was observed. Mean time between the onset of the disease and diagnosis was nine years. Hurley stage II was the most common at diagnosis. The therapeutic option mostly used in Hurley I and II was systemic antibiotics and in Hurley III was surgery. Study limitations: the main limitation of this study is its retrospective design, which does not allow the true clinical confirmation of the disease by investigators. Conclusion: we outlined the following profile: women, caucasian, between 3rd and 4th decade of life, associated with obesity, smoking, late diagnosis and multiple potential therapeutic modalities. We highlight the importance of studies like this in order to identify risk groups and encourage early diagnosis.